(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim- Retention of cement retained implant prosthesis to the abutment is important for the longevity and function of prosthesis and thus the die preparation for the fabrication of the prosthesis should be accurate. Aim of this study is to compare the retention values of implant supported crown obtained by laser metal sintering technique fabricated on gypsum abutment and epoxy resin abutment dies. Material and methods- Dies were fabricated (n=40) after making impression with polyether. 20 dies were made from epoxy resin die material (group 1) and 20dies from gypsum die material Group 2. CAD CAM designed, DMLS crowns were fabricated by scanning the dies and the prosthesis cemented on the abutments using zinc phosphate cement. Retention value was obtained by applying constant tensile load at cross head speed of 0.5mm/minute in pull direction until the copings separated on the universal testing machine. Statistical analysis was done using t test.Observation and result- The value of retention for epoxy resin die prosthesis was higher than the value of gypsum die(p>0.05). Conclusion- Epoxy resin dies are more dimensionally accurate than gypsum dies for cement retained implant prosthesis.